Electrodynamic balance–mass spectrometry reveals impact of oxidant concentration on product composition in the ozonolysis of oleic acid. Issue 44 (3rd November 2022) - Müller, Marcel; Mishra, Ashmi; Berkemeier, Thomas; Hausammann, Edwin; Peter, Thomas; Krieger, Ulrich K.
Abstract : Electrodynamic balance–mass spectrometry measurements reveal how the ozone concentration influences the product composition of oleic acid aerosol droplets. Abstract : The chemical and physical properties of atmospheric aerosol particles change upon oxidative ageing, influencing their interaction with radiation, their propensity to serve as nuclei for cloud condensation and ice formation, and their adverse effects on human health. The investigation of atmospheric aerosol oxidation processes is complicated by low oxidant concentrations and long timescales, which are difficult to represent in laboratory studies. Experimental work often attempts to compensate for short timescales with elevated concentrations of oxidative agents, assuming that the ageing progress depends only on the oxidant exposure, i.e. on the product of oxidant concentration and time, [Ox] × t, and not on [Ox] or t independently. The application of electrodynamic balance–mass spectrometry of single particles allows the validity of this assumption to be investigated, since it provides information on the molecular composition of aerosol particles for a wide range of reaction durations under well-defined oxidation conditions. Here, we demonstrate the capabilities of a new setup on levitated oleic acid droplets reacting with ozone at mixing ratios of 0.2 and 15 ppm, i.e. spanning almost two orders of magnitude in [Ox]. We show that the reactive removal of oleic acid can be accurately expressed as a function of ozone exposure [Ox] × t, whereas the product concentrations depend on [Ox] and t independently. As the underlying reason for the breakdown of the exposure metric, we suggest a competition between evaporation of volatile first-generation products and their accretion reactions with reactive Criegee intermediates, converting them into low-volatility dimers and oligomers. This hypothesis is supported by kinetic model simulations using the aerosol process model KM-SUB, which explicitly resolves the competition between evaporation and secondary chemistry as a function of the experimental timescale and ozone mixing ratio. The model successfully reproduces final product distributions. The findings are further supported by the recorded changes of droplet sizes during oxidation. As a heuristic, the breakdown of the exposure metric in a chemical reaction system is possible, when competition between first- and second-order processes of reactive intermediates determines important system properties.